Comparative analysis of the influence of Chinese urban and rural family cultures on household financial asset allocation - Li, Zhisheng; Mirko, Cucci; D’Agostino, Maria Teresa; Jin, Jiyang (Frontiers in Psychology, 2023)
Despite the national strategic priority to achieve common prosperity, there still exist prominent discrepancies in financial asset allocation between Chinese urban and rural families, which requires a deeper, more comprehensive investigation. To fill this gap, the present research adopted a cultural perspective to investigate relevant issues by addressing the cognitive differences of residents between urban and rural families. Under the analytical framework of Hofstede's cultural values, this paper discusses the cognitive differences between urban and rural families in terms of financial asset allocation in the cultural dimensions of collectivism, individualism and uncertainty avoidance; hypotheses are accordingly developed. In terms of research methods, the data of the China Family Panel Studies (CFPS) were used in the probit model to investigate the influence of urban and rural family cultural differences on household financial asset allocation. The results of this paper are as follows: (1) family cultural values have a positive impact on family financial asset allocation. (2) knowledge acquisition plays an intermediary role in family cultural values and family financial asset allocation. (3) and for rural families with high collectivism and uncertainty avoidance, the mediating effect is more prominent. This paper provides a new perspective for exploring the possibility of household asset allocation from the perspective of cultural psychology. The contribution of this paper have theoretical and practical reference significance to narrow the wealth gap between urban and rural areas and achieve common prosperity.